Pengembangan Sistem Pencatatan Kehadiran dengan Pembatasan Area Login Berbasis Web - Anie Rose Irawati; Dwi Sakethi; Robby Hernanda (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2014)
Online attendance list is one of the new breakthroughs to record the list of attendees using computer technology and internet. In general, online attendance list is done by entering the username and password that have been registered in the system within the limited area. This research developed a web based attendance recording system with login area restriction. The system not only will check the username and password entered by user but also detecting the IP addresses to see whether they allowed to access the system or not. If the users succeed login to the system, it also means that they will be listed in the presence list and if they fail the system will not record their presence. The system produce the report of attendance list for given period and can also be used to protect information access Keywords: attendance list, information systems, ip address, login area restriction.